2016
DOI: 10.1136/postgradmedj-2016-134071
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment among patients with multiple sclerosis: associations with employment and quality of life

Abstract: BICAMS provides a sensitive and easy to administer screening test for cognitive impairment within the outpatient setting. Cognitive impairment is common in our cohort of patients with MS attending outpatients and appears to be associated with increased rates of unemployment and lower measures of QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 28 publications
3
73
0
5
Order By: Relevance
“…34 These data suggest that NEDA status does not preclude cognitive deterioration, and cognitive evaluation should be included in the NEDA composite measure. 35,36 Also, cognitive impairment seen at the time of MS diagnosis increases the risk of changing vocational status within 7 years. 4 One area in which this negative effect is very apparent is the patient's employment situation.…”
Section: Cognition In Msmentioning
confidence: 99%
See 3 more Smart Citations
“…34 These data suggest that NEDA status does not preclude cognitive deterioration, and cognitive evaluation should be included in the NEDA composite measure. 35,36 Also, cognitive impairment seen at the time of MS diagnosis increases the risk of changing vocational status within 7 years. 4 One area in which this negative effect is very apparent is the patient's employment situation.…”
Section: Cognition In Msmentioning
confidence: 99%
“…4 One area in which this negative effect is very apparent is the patient's employment situation. 36 Furthermore, it was reported that the Symbol Digit Modalities Test (SDMT) was the most significant predictor of unemployment among patients with MS. 35 Cognitive difficulties also hamper disease management, including decision-making, medication adherence, symptom control and rehabilitation benefit. 35,36 Also, cognitive impairment seen at the time of MS diagnosis increases the risk of changing vocational status within 7 years.…”
Section: Cognition In Msmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also found that psychosocial factors such as lower coping, negative mood, reduced self-efficacy, and decreased perceived support effect their life and eventually lead to reduced quality of life in people with MS (Farran, Ammar, & Darwish, 2016). In addition, several studies have found that neuropsychiatric complications such as cognitive impairments and fatigue have major effect on their life (Campbell, Rashid, Cercignani, & Langdon, 2017). In general, the disease characteristics in terms of disabling physical symptoms augmented by the psychological and neuropsychiatric complications often makes this population feel isolated, deprived, and perceived as being stigmatized.…”
Section: Introductionmentioning
confidence: 99%